Thermodynamic description of phase equilibrium in systems MCl5–M’Cl5, (M = Nb, Ta, Mo, W, Re) and MCl3–M’Cl3, (M = Ln) - A. V. Galantsev; D. V. Drobot; L. V. Yanshina (Тонкие химические технологии, 2011)
The paper considers the Saint-John-Bloch model and proves that this model is applicable for describing phase equilibrium in binary systems formed by pentachlorides of d-elements of groups V, Vl, Vll of the periodic system and lanthanide chlorides. The dependence of the possibility of forming solid solutions in LnCl3-Ln'Cl3 on the atomic number of a lanthanide was found.